Childhood adversity, mental health, and the perpetration of physical violence in the adult intimate relationships of women prisoners: A life course approach. (March 2020) - Jones, Melissa S.; Burge, Stephanie W.; Sharp, Susan F.; McLeod, David A.
Abstract: Background: Adverse childhood experiences (ACEs) are common, with nearly two-thirds of adult samples reporting exposure to at least one and one-quarter reporting exposure to three or more distinct types of ACEs. ACEs have been linked to various negative outcomes across the life course, including mental health problems, and the perpetration of physical violence in intimate relationships. However, little is known about the relationships between ACEs, PTSD symptomology, and use of physical violence against an adult intimate partner among incarcerated women. Objective: The purpose of this paper is to examine the relationships between ACEs, PTSD symptoms, and the perpetration of the physical violence in the adult intimate relationships of women prisoners. Methods: Using data from the 2014 Oklahoma Study of Incarcerated Mothers and Their Children ( N = 349) and structural equation modeling (SEM) techniques, we investigate the potential mediating effect of PTSD symptoms in the relationship between ACEs and perpetrating violence against an intimate partner. Results: Our findings indicate that PTSD symptomology fully mediates the relationship between ACEs and the perpetration of physical violence against an adult intimate partner, indicating that PTSD experiences may be central to understanding women's pathways toward violence. Conclusions: Women prisoners who were exposed to ACEs during childhood were at a particularly elevated risk of developing PTSD symptomology and perpetrating physical violence against an adult intimate partner. Based on the current study's findings, treatment programs that address these complex relationships between ACEs, particularly focusing on the central role of mental health in these processes, are needed for incarcerated women.